2008
DOI: 10.1097/prs.0b013e31817151f8
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and Venous Anatomies of the Deep Inferior Epigastric Perforator and Superficial Inferior Epigastric Artery Flaps

Abstract: This study demonstrates that flow through medial and lateral row perforators occurs in physiologically stereotyped patterns. A medial row perforator should be selected if zone IV perfusion is required. The SIEA was consistently seen to only perfuse a hemiflap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 26 publications
3
90
0
8
Order By: Relevance
“…[3][4][5][6][7] Anatomic studies have shown that the deep inferior epigastric vein (DIEV) connects with the superficial inferior epigastric vein (SIEV) through a system of choke vessels within the flap. [8] In numerous studies, the superficial venous system has been used to adequately decongest the flap in cases where venous congestion was clinically observed [9][10][11][12][13]. We have found that routinely anastomosing both the superficial and deep venous systems has resulted in significantly fewer operative take-backs and decreased venous complications with use of the DIEP flap.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…[3][4][5][6][7] Anatomic studies have shown that the deep inferior epigastric vein (DIEV) connects with the superficial inferior epigastric vein (SIEV) through a system of choke vessels within the flap. [8] In numerous studies, the superficial venous system has been used to adequately decongest the flap in cases where venous congestion was clinically observed [9][10][11][12][13]. We have found that routinely anastomosing both the superficial and deep venous systems has resulted in significantly fewer operative take-backs and decreased venous complications with use of the DIEP flap.…”
Section: Introductionmentioning
confidence: 83%
“…A system of choke vessels exists between the superficial inferior epigastric vein and the deep inferior epigastric system; however, certain variations in anatomy may exist. [8] Venous branches crossing the midline have been found to be absent in 36% of cases [4,14]. This paucity of crossing branches explains why survival of Zone IVof the flap can be quite unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Estudos experimentais sobre a vascularização dos vários retalhos miocutâneos e seu território vascular, principalmente do plexo da epigástrica inferior, contribuíram consideravelmente para melhores resultados. [3][4][5][6][7] Alguns trabalhos utilizaram fármacos para avaliar a perfusão e a necrose desses retalhos. 8 Assim, para efetuar uma maior vascularização nesses retalhos, alguns cirurgiões começaram a realizar a "flap delay" (autonomização) 7,9-10 em referência ao chamado "delay phenomenon".…”
Section: Introductionunclassified
“…Despite the potential benefits, the use of this flap has been limited in breast reconstruction when compared with the deep inferior arterybased flaps. Cited reasons for this include: that typical perfusion only supports an ispilateral hemiabdomen (3,(5)(6)(7); the SIEA vessels have been cut preoperatively in many cases due to previous pfannenstiel incisions; and the diameter of the artery is believed to be of insufficient size to reliably complete a successful microvascular anastomosis. The highest reported rate of use of the SIEA flap versus the DIEA-based flaps has been in the 30% range (3,5,8,9).…”
mentioning
confidence: 99%